Dependence of Local People and Issues in Conserving Local Resources : Case of Dalma Wildlife Sanctuary, Jharkhand - Srivastava, Sanjay (Indian Forester, 2006)
The management of Protected Areas is increasingly becoming complex due to high pressure of people living in and around them. Upgrading of PA management inputs requires a fuller understanding of both biological well as sociological issues. This assumes greater importance in high human density regions. It is now becoming clear that PAs in such areas need detailed studies in tandem with a documentation of biotic pressure profile in order to fully assimilate the new participatory approaches to the management. This paper deals with a case study of Dalma Wildlife Sanctuary in the newly created State of Jharkhand where local communities in and around the sanctuary have organized themselves in form of informal village Forest Protection Committees and controlled the grazing of cattle, illicit felling and annual tribal hunt and catalyzed the natural regeneration without much financial support. However there are sustained losses to local communities from the Govt. policies of wildlife management and the laws governing the protected areas. The study shows that there is a strong requirement for the institutional arrangements for the sanctuary which can safeguard the interests of local communities and ensure their participation in the protection of wildlife for conservation of sanctuary’s resources